Empreendedorismo feminino: uma análise socioeconômica das mulheres empreendedoras do Mercado Municipal de Tabatinga-Amazonas - Silva, Deiviane Maricaua da (Brasil, 2023)
Many women see in entrepreneurship the opportunity of financial independence, so it is notorious the female presence in all branches of the labor market, including fairs and markets. The general objective of the present study was to investigate the reasons that influence women entrepreneurs to sell their products in the Municipal Market of Tabatinga-Amazonas. The technical procedures of the research involved bibliographic and documental survey, in addition to field research, conducted through interviews with thirty-five market women who were willing to spontaneously participate in the research. The results of the research show that the participants are women aged between 21 and 70 years, most are single, have high school as the highest level of education, work in the market for over 5 years and obtain a maximum monthly income of up to R$ 1,500.00. Among the main reasons that influence them to work as market vendors, the necessity was the most prominent reason, as well as the lack of experience to work in another segment. As challenges to perform their daily activities, issues related to infrastructure and logistics stood out as the main challenges. In this sense, it is concluded that entrepreneurship provides diverse opportunities for the financial achievement of women, and fairs and markets are environments of great commercial potential and social inclusion, allowing market women to be economically active and be able to realize themselves and provide for their families.